Educational Leader’s Peculiarities under Highlights of Holy Quran - Hemn Taher Darwesh; Jawad Faqi Ali Chomhaydari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The present research investigates about (Educational Leader) under highlights of Holy Quran. It is an attempt to clarify significant and dimensions of (Educational Leader) with Quranic guidelines, and scientific research principles and methods. This attempt comes after observing and penetrating those references which are related to the Holy Quran, the Quranic explanations and Prophet Mohammed’s (peace be upon him) hadiths, despite those perspective books which full of educational subjects, even those which cares about (Educational Leader). Moreover, this research, with explaining the term of (Educational Leader), also highlights on characteristics, attitudes, and conditions of (Educational Leader), meanwhile, it talks about its qualities and brainy. All these are collected in two parts and five subjects, specifically, the subjects of this research are most significant components of (Educational Leader), with respect for the Holy Quran, wises, professors, and researchers in the area of (Educational Leader). In the end, we mentioned the outcomes and suggestions of the research.